Cement-based mortars production applying mining residues treated with an electro-based technology and a thermal treatment: Technical and economic effects. (19th April 2021) - Almeida, J.; Faria, P.; Ribeiro, A.B.; Santos Silva, A.
Highlights: Mining residues were submitted to an electrodialytic process alone or coupled with a thermal treatment. Treated mining resides replaced cement from 10 to 50 wt% in mortars. Flexural strength of mortars decreased from 3 to 52%, showing potential for renders. Mortars' cost-efficiency with only electrodialytic treatment could be upgraded. Abstract: The combination of treatments may improve the extraction of toxic and critical elements from secondary resources, produce changes in materials' physico-chemical properties and improvements on the sustainability of strategies. Mining residues were treated with an electrodialytic process alone or coupled with a thermal procedure, and reused in cement-based mortars by replacing 10, 25 and 50% of the cement binder content. This study demonstrated the technical and economic feasibility of mortars produced with treated mining residues, namely in applications where flexural strength is key factor. The mechanical properties of the mortars corroborated their compatibility with bedding mortars and fired brick masonry walls.